JENIS DAN KEANEKARAGAMAN FITOPLANKTON DI WADUK PLTA KOTO PANJANG, KAMPAR, RIAU - Siagian, Madju (Bumi Lestari; Vol 12 No 1 (2012), 2012)
A study on the type and phytoplankton diversity in the Koto Panjang Dam, Kampar, Riau , was conducted on May-October 2009. There were 6 stations, in the Batu Basurat, Koto Tuo , Tanjung Alai, Batang Mangat and Rantau Berangin villages and in the river mouth of the Kampar River. Parameters measured were water quality in general and phytoplankton diversity. In each station, water and phytoplankton samples were taken in the surface, 2.5 secchi depth and in the bottom of the dam. Sampling was conducted once/ month. Types, abundance and diversity of phytoplankton were analyzed. Results shown that there were 17 species of phytoplankton that were belonged to 4 classes, namely Bacillariophyta (6 species), Chlorophyta (5 species), Crysophyta (3 species) and Cyanophyta ( 3 species). There were no dominant species in the research area, good diversity index (2.13-2.71) and high similarity index (0.81-0.94). Based on data obtained, it can be concluded the water quality in the Koto Panjang Dam is suitable for supporting the life of phytoplankton.
Keywords: Koto Panjang Dam; phytoplankton diversity; Kampar River; Riau